#TITLE_ALTERNATIVE# - ARMILAH (NIM 20506055), MIA
Electrochemistry is one of difficult topic in Chemistry course, which can reduce student enthusiasm to study electrochemistry. A learning strategy is needed to motivate students. A context-based learning using examples familiar to students is given as an approach. Battery represents one of the aplication of Voltaic cell. In this work, analysis of factors that influence the performance of fruit and vegetable battery was carried out, and the results were used to design experimental module and electronic learning (e-learning). Fruit and vegetable, such as limes, potatoes, and marquisa, were used to make up the battery. Its performance was measured using two parameters, namely the capacity and the voltage. The voltage was evaluated as a function of electrode's distance, surface area of electrodes, and discharge's time. Voltage as a function of surface area of electrode is used to determine a current density, and, voltage as a function of discharge's time is used to determine battery capacities. Experimental results shows that the voltage of battery is around 0,9 V, and have a small capacity. The capacity range is from 1,8228 mA.menit to 20,4867 mA.menit. This experiment is used as a foundation to create experimental module. This is a simple expriment that can be provided to the students that a battery can be constructed using vegetables and fruits as electrolytes. It will be interesting for students because the experiments use materials which might not be imagined by them. The experiment's module was uploaded to LMS, in this case MOODLE (Modular Object-Oriented Dynamic Learning Environment), which is an open-source software. Moodle have facilities for teaching-learning such as course material, assignment and quiz.